Laparoscopic resection of a giant post-mesenteric ovarian seromucinous cystadenoma: a case report and review - Chen, Hong; Ye, Yifan; Liu, He; Huang, Rui; Li, Ningbo; Tang, Yaling (Frontiers in Oncology, 2025)
BackgroundOvarian seromucinous tumors represent a rare subclass of ovarian neoplasms. While the majority of these tumors are benign, the potential for malignant transformation persists and should be considered. To enhance patient outcome and mitigate the risk, early detection and timely intervention are paramount. In cases involving large or complex ovarian masses, open surgery is often the preferred approach, as it provides superior access for comprehensive tumor resection and enables immediate histopathological evaluation. Nevertheless, with advancements in laparoscopic techniques, single-port laparoscopic surgery has emerged as a viable alternative for patients. This approach not only demonstrates comparable effectiveness but also offers the benefits of expedited recovery and reduced scarring.Case reportA 65-year-old female presented with a seven-month history of abdominal distension, a sensation of fullness beneath the xiphoid, left-sided discomfort, and intermittent morning cramping. Laboratory findings revealed a mild elevation in CA-125 to 46 U/mL, and CT imaging suggested a diagnosis of an ovarian cystadenoma or possibly a retroperitoneal mass. Preoperative assessment was challenging due to the tumor’s irregular morphology, substantial size, and its adhesions to surrounding pelvic and abdominal structures, making it difficult to precisely determine its origin. In light of these complexities, a single-port laparoscopic approach was chosen to minimize trauma, allow for more precise handling of the tumor, and reduce the risk of cystic fluid leakage or inadvertent dissemination of the tumor. Postoperative pathological examination confirmed the lesion to be a seromucinous ovarian cystadenoma.ConclusionThis case exemplifies the imperative for a multidisciplinary approach in the diagnosis and treatment of ovarian seromucinous tumors, emphasizing the advantages of minimally invasive surgical techniques. Given the rarity of such tumors, it is essential that ongoing research into the pathogenesis, classification, and treatment strategies be prioritized to enhance patient outcomes.